Combination therapy with PTH and DBM cannot heal a critical sized murine femoral defect. Issue 8 (14th May 2015) - Pensak, Michael; Hong, Seung‐Hyun; Dukas, Alex; Bayron, Jennifer; Tinsley, Brian; Jain, Ashish; Tang, Amy; Rowe, David; Lieberman, Jay R.
ABSTRACT Orthopaedic surgeons continue to search for cost‐effective bone graft substitutes to enhance bone repair. Teriparatide (PTH 1‐34) and demineralized bone matrix (DBM) have been used in patients to promote bone healing. We evaluated the efficacy of PTH and DBM in healing a critical sized femoral defect in three lineage‐specific transgenic mice expressing Col3.6GFPtopaz (pre‐osteoblastic marker), Col2.3GFPemerald (osteoblastic marker) and α‐SMA‐Cherry (pericyte/myofibroblast marker). Mid‐diaphyseal defects measuring 2 mm in length were created in the central 1/3 of mice femora using a circular saw and stabilized with an alveolar distractor device and cerclage wires. Three groups were evaluated: Group I, PTH 30 μg/kg injection daily, Group II, PTH 30 μg/kg injection daily + DBM, and Group III, DBM + 30μL saline injection. PTH was given for 28 days or until the time of sacrifice. Animals were sacrificed at 7, 14, 28, and 56 days. Radiographs at the time of sacrifice were evaluated using a 5‐point scaled scoring system. Radiographs showed a lack of healing across all treatment groups at all time points: Group I, 1.57 +/− 0.68; Group II, 3.00 +/− 1.29; and Group III, 2.90 +/− 1.03. Bone formation in the defect as measured by radiographic healing score was significantly better at 56 days in Groups II (p = 0.01) and III (p < 0.01) compared to Group I. Across all treatment groups and time points the defects were largely absent of osteoprogenitor cells based on gross observation of frozen histology and quantitation of cellular based histomorphometric parameters. Quantitation of frozen histologic slides showed a limited osteoprogenitor response to PTH and DBM. Our results suggest that the anabolic agent teriparatide is unable to induce healing in a critical sized mouse femoral defect when given alone or in combination with the DBM preparation we used as a local bone graft substitute. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1242–1249, 2015.